Complexity and artificial markets - Schredelseker, Klaus. (Lecture Notes in Economics and Mathematical Systems,)
Market mechanisms - Zero-intelligence trading without resampling - Understanding the price dynamics of a real market using simulations: the dutch auction of the pescara wholesale fish market - Market behavior under zero-intelligence trading and price awareness - Evolution and decision making - Evolutionary switching between forecasting heuristics: an explanation of an asset-pricing experiment - Prospect theory behavioral assumptions in an artificial financial economy - Computing the evolution of walrasian behaviour - Multidimensional evolving opinion for sustainable consumption decision - Information economics - Local interaction, incomplete information and properties of asset prices - Long-term orientation in trade - Agent-based experimental economics in signaling games - Methodological issues - Why do we need ontology for agent-based models? - Production and finance in eurace - Serious games for economists - Invited speakers - Computational evolution - Artificial markets: rationality and organisation.